Local Worldmaking Through Little Dragons for a Better World: A Case Study of a Intercultural Community Building Project - Meng, Vanessa (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
This article presents a case study in grassroots aesthetic education as world-making within a diaspora Chinese community in the United States. This experimental education acted as a pedagogy of resilience in the face of the pandemic and its revealing of structural injustices. For American-Chinese and Chinese-American students, this education provided a way to understand themselves as inhabiting multiple identities, a re-orientation urgently needed in the context of politicized U.S.-China relations during and after the pandemic. Encouraging creativity and the arts as methods to bridge identities and communities, Little Dragons for a Better World also established new pathways for resource sharing and care relationships. The article situates this education in theories of activism drawn from Grace Lee Boggs, Angela Davis, Wangari Maathai, Urmi Basu, Hu Mama, Thich Nacht Han, Arundhati Roy, and Giovana Di Chiro, orienting community-building at the local scale as a revolutionary practice.